Guarding Sharia Economy in Indonesia Optimization of Contemporary Ulama Authority and Local Wisdom - Muhammad Djakfar (UIN Maulana Malik Ibrahim Malang, 2017)
Sharia economy is one of the economic system, in addition to the other two systems namely capitalist and socialist. Although the socialist system is no longer popular at the global level, but in reality the Sharia Economy system is still outdone by the secularistic capitalist system. In practice, the capitalist system contains many weaknesses so that the world community began to look for other systems as a solution, namely sharia economy. In Indonesia the development system is relatively slow, so it is necessary to optimize the role of ulama and the function of local wisdom. This is the literature research with data sources from various literature and relevant issues. The results of the study show that with its authority, contemporary ulama can perform the role as a giver of fatwas, enlighteners, thinkers and economic actors. Enlightenment can be done through religious or educational events, while business practices can be conducted in pesantren by developing businesses, all of which are part and function of local wisdom.Ekonomi syariah adalah merupakan salah satu sistem ekonomi, di samping kedua sistem yang lain yakni kapitalis dan sosialis. Sekalipun sistem sosialis akhir-akhir ini tidak lagi populer di tingkat global, namun dalam kenyataan sistem ekonomi syariah masih kalah cepat dengan sistem kapitalis yang sekularistik. Dalam praktiknya, sistem kapitalis mengandung banyak kelemahan sehingga masyarakat dunia mulai mencari sistem lain sebagai solusi, yakni ekonomi syariah. Di Indonesia sistem ini perkembangannya relatif lambat sehingga perlu mengoptimalkan peran ulama dan fungsi kearifan lokal. Wacana ini merupakan penelitian pustaka dengan sumber data dari berbagai literatur dan isu yang relevan. Hasil kajian menunjukkan bahwa dengan otoritasnya, ulama kontemporer dapat melakukan peran sebagai pemberi fatwa, pencerah, pemikir dan pelaku ekonomi. Pencerahan dapat dilakukan melalui acara keagamaan atau pendidikan, sedangkan praktik bisnis dapat dilakukan di pesantren dengan mengembangkan usaha, yang semuanya itu merupakan bagian dan fungsi dari kearifan lokal.